On Research of Cable Tension Distribution Algorithm for Four Cables - Three DOF Planar Cable-Driven Parallel Robot - Dao, Cong Hoang Kha; Tuong, Phuoc Tho; Vu, Ngoc Duc; Nguyen , Minh Nhat (Journal of Technical Education Science, 2023)
One of the main concerns in controlling the cable-driven parallel robot (CDPR) mechanism is dealing with the distribution of tension on each cable, which is critical to the operation of the entire cable system. It can be said that adjusting the cable tension will determine the power consumption of the motors and the stiffness of the structure. Therefore, the problem that needs to be solved is how to handle the cable tension when the end-effector moves throughout the entire workspace. The tension of each cable needs to be adjusted properly to ensure it remains the same. Moment and force act in a static state, keeping the kinematic position of the end moving platform from being deflected and the main purpose is to ensure that the robot achieves a rigid state and eliminates vibration when moving. Because of that essential demand, this article will refer to the Quadratic programming algorithm to solve the problem of tension distribution for the Planar Cable-Driven Parallel Robot consisting of 4 cables with 3 degrees of freedom. This article will be the foundation for applying this algorithm to an 8-cable robot with 6 degrees of freedom (Spatial Cable-Driven Parallel Robot for example). At the same time, in this article, the simulation results for the algorithm will also be presented in this paper.